Exhibition and Description of a Collection of Stone and other Remains from Swiss Lake Dwellings, illustrative of the Agriculture, Manufactures, &c., of the Lake Dwellers (Proceedings of the Society of Antiquaries of Scotland, 1871)
Lord Rosehill exhibited some of the artefacts he collected on his trip to Switzerland. These artefacts were collected at the site of Stone Age lake-dwellings in the Swiss Alps. Lady Rosehill also provided a list of plant seeds collected at the sites. Professor Simpson thanked Lord Rosehill for his talk and added some further remarks on the sites from his own visit. Meeting notes for 14 March, 1870 are appended. At this meeting, Lady Alicia Ann Scott (referred to as Lady John Scott) was elected as the Society’s first Lady Associate.